2007
DOI: 10.1093/annonc/mdm221
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib: bridging present and future cancer treatment

Abstract: Tyrosine kinase receptors (RTKs) are a heterogeneous group of transmembrane proteins involved in signal transduction. These receptors are expressed in many different cells and regulate cellular growth, differentiation and angiogenesis. Overexpression and/or the structural alteration of different RTKs classes are generally associated to cancer and, when RTKs-mediated signal transduction pathways are abnormally activated, generate cancer growth, angiogenesis and metastatization. Therapeutic intervention targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…25 Significantly, the multi-kinase inhibitor sunitinib, which targets many of the same kinases as sorafenib (vascular endothelial growth factor receptor 1, 2, and 3; platelet-derived growth factor receptor; c-kit; FMS-like tyrosine kinase 3; and RET tyrosine kinase) but not RAF, does not result in development of SCCs or KAs. 13,26 Sorafenib is a nonselective inhibitor of wild-type and mutated forms of RAF, with poor activity against BRAF V600E tumor cells, and has been demonstrated to be an ineffective treatment for melanoma. 7,27 An estimated 6% to 7% of patients treated with sorafenib develop SCCs and KAs, which stands in contrast to 20% to 30% of patients taking vemurafenib.…”
Section: Discussionmentioning
confidence: 99%
“…25 Significantly, the multi-kinase inhibitor sunitinib, which targets many of the same kinases as sorafenib (vascular endothelial growth factor receptor 1, 2, and 3; platelet-derived growth factor receptor; c-kit; FMS-like tyrosine kinase 3; and RET tyrosine kinase) but not RAF, does not result in development of SCCs or KAs. 13,26 Sorafenib is a nonselective inhibitor of wild-type and mutated forms of RAF, with poor activity against BRAF V600E tumor cells, and has been demonstrated to be an ineffective treatment for melanoma. 7,27 An estimated 6% to 7% of patients treated with sorafenib develop SCCs and KAs, which stands in contrast to 20% to 30% of patients taking vemurafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CSF-1R blockade may be a promising therapeutic approach for some, but not all, malignant tumors. It is worth noting that Sunitinib, a multi-targeted receptor tyrosine kinase inhibitor, that targets the CSF-1R along with many other receptor tyrosine kinases, is a first-line therapy for advanced RCC (1,48,49). Taken together, our findings clearly indicate that targeting the CSF-1R is a potential therapeutic for human RCC.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Sunitinib targets selectively VEGF, KIT, FLT3, RET, PDGFRA, and PDGFRB 36,37 and the fact that CSF1R shares structural and organizational homology with those receptor tyrosine kinases suggests a relevant role of CSF1R as a target of sunitinib in renal cell carcinoma patients. Furthermore, recent studies using hematopoietic colony assays demonstrated that imatinib targets CSF1R at therapeutic concentrations, 38,39 further indicating that CSF1R may represent a future valuable therapeutic target of receptor tyrosine kinase drug inhibitors in renal cell carcinoma patients.…”
Section: Discussionmentioning
confidence: 99%